STRATEGI GURU DALAM MENGATASI PERILAKU AGRESIF PADA ANAK USIA 4-6 TAHUN DI TK TARBIYAH ISLAMIYAH TEBAS TAHUN PELAJARAN 2022-2023 - Amira, Dienda; Aslan; Multahada, Asyruni (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
The aim of this research is to describe and find out about: 1) forms of aggressive behavior carried out by children aged 4-6 years at Tarbiyah Islamiyah Tebas Kindergarten; 2) teacher strategies in dealing with aggressive behavior in children aged 4-6 years at Tarbiyah Islamiyah Tebas Kindergarten. This research uses a qualitative approach and the type of research used is a qualitative method with a case study approach. The data collection techniques used were observation, interviews and documentation. Then the data analysis techniques used in this research are data reduction, data display/data presentation, and drawing conclusions. Meanwhile, the technique for checking the validity of the researcher's data uses triangulation techniques and member checks. The results of this research show that: 1) Forms of aggressive behavior in children aged 4-6 years are as follows: a) predatory aggressive behavior such as kicking their friends with their feet, hitting their friends using objects and hands, pushing their friends' heads or limbs and biting. his friend's hand; b) aggressive behavior between males such as shouting at his friend with a loud voice and splashing his friend's face with water; c) offended aggressive behavior such as throwing chairs and throwing books; d) aggressive defensive behavior such as disturbing friends who are passing in front of them and disturbing friends who are studying; e) instrumental aggressive behavior of attacks that ends up hurting another person in an action and hitting a friend until he is injured. 2) The strategies used are the methods used by teachers in organizing and planning learning activities during the learning process in class. Teachers should pay attention to students with aggressive behavior, namely by marking the child in what way he experiences aggressive behavior and placing students with children who do not experience aggressive behavior, sitting in a place that has been controlled by the teacher, a system of approaches or actions carried out by the teacher, are as follows: a. expository learning strategies; b. heuristic learning strategies; c. reflective learning strategies.